McCormack on managing - McCormack, Mark H. (Arrow Business, 1996)
Based on the author's wide-ranging managerial experience as a successful entrepreneur, this book looks at the fundamentals of managing people, money, the job, crises, and growth. It is one of a series of business books in which McCormack focuses on key disciplines and shares his philosophy.